3D hollow-structured hydrogels with editable macrostructure, function, and mechanical properties induced by segmented adjustments. Issue 43 (5th August 2021) - Wang, Qinhua; Yu, Jing; Lu, Xingmei; Cao, Shilin; Chen, Lihui; Pan, Xiaofeng; Ni, Yonghao; Ma, Xiaojuan
Abstract : The segmental adjustment of the microstructure of the hydrogel by the combination of plasticizer and freeze–thaw enables the PVA–borax hydrogel to achieve plasticine-like plasticity and rubber-like strength successively. Abstract : Currently, it is challenging to prepare uniform hollow-structured hydrogels with tailorable comprehensive properties. Herein, making full use of the different gelation routes of polyvinyl alcohol (PVA), we propose a distinctive two-stage method for preparing hollow-structured hydrogels, which is to arrange the microstructure of the hydrogel through segmented adjustment. The mechanical properties, macrostructure, and functions of the obtained hollow hydrogel can be easily designed and edited. Specifically, the mechanical properties of the hollow hydrogel can be improved from "soft" to "hard" by changing the preparation conditions. In addition, hollow hydrogels with diverse macrostructures can also be developed through different templates, such as tubes, gloves, and rings. More importantly, the hollow hydrogels can be endowed with conductive, anti-drying, anti-freezing, and photothermal-converting functions due to the great system compatibility of the gel precursor. Benefiting from the advantages of the hollow hydrogel, the conductive gel ring-based bioelectrodes and sensors were developed. Interestingly, the adaptive gel ring-based electronics can stably record the electrophysiological and strain signals of the human body without the help of adhesive tape. This study opens more opportunities for development and applications of other hydrogel-based hollow materials.